2023
DOI: 10.1101/2023.12.07.570640
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell eQTL mapping in yeast reveals a tradeoff between growth and reproduction

James Boocock,
Noah Alexander,
Leslie Alamo Tapia
et al.

Abstract: Expression quantitative trait loci (eQTLs) provide a key bridge between noncoding DNA sequence variants and organismal traits. The effects of eQTLs can differ among tissues, cell types, and cellular states, but these differences are obscured by gene expression measurements in bulk populations. We developed a one-pot approach to map eQTLs inSaccharomyces cerevisiaeby single-cell RNA sequencing (scRNA-seq) and applied it to over 100,000 single cells from three crosses. We used scRNA-seq data to genotype each cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 106 publications
(151 reference statements)
0
5
0
Order By: Relevance
“…Recently, it was shown that a single point mutation in the GPA1 gene (W82R) reduces fitness and induces a higher mating efficiency [50]. We found that 6 Mata strains (YAB1, YCH1, YCH2, AST1, CGL1, CPK1) and 1 Matα (AST) strain from our collection have this mutation.…”
Section: Selected Hybrids In Each Condition Are Made Either More Than...mentioning
confidence: 60%
See 1 more Smart Citation
“…Recently, it was shown that a single point mutation in the GPA1 gene (W82R) reduces fitness and induces a higher mating efficiency [50]. We found that 6 Mata strains (YAB1, YCH1, YCH2, AST1, CGL1, CPK1) and 1 Matα (AST) strain from our collection have this mutation.…”
Section: Selected Hybrids In Each Condition Are Made Either More Than...mentioning
confidence: 60%
“…In conditions where cell size is crucial for cell fitness, haploid cells tend to choose partners whose cell size aligns more closely with the optimal size for fitness in that particular condition [24]. A recent study by Boocock et al [50] showed that a single point mutation that changes a tryptophan to arginine in the GPA1 gene reduces fitness of the strains, but increases their mating efficiency. Moreover, this mutation was also associated with increased outbreeding tendency of natural strains.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, eQTL mapping with snRNA-seq is also possible in F2 populations, provided sufficiently high numbers of individuals are used as input. This has been demonstrated in Caenorhabditis elegans (Ben-David et al, 2021) and Saccharyomyces cerevisiae (Boocock et al, 2023) using highly recombined F4 populations, opening up the possibility of mapping eQTLs using only single cell RNA-seq in cell-types other than haploid gametes. Furthermore, other single cell sequencing modalities, such as assay for accessible chromatin (ATAC) sequencing or DNA methylation sequencing (Heumos et al, 2023) also provide molecular phenotypes which could then be linked to haplotype information.…”
Section: The Broader Applications Of Qtl Mapping Using Genetically He...mentioning
confidence: 99%
“…However, all cells derived from the same individual share the same genotype, meaning that the resolution and power of the eQTL analysis is limited to the number of individuals used in the pool, rather than the number of cells in the dataset. The use of cell populations with greater genetic heterogeneity, such as recombinant haplotypes in gametes, or large populations of segregants (Ben-David et al, 2021;Boocock et al, 2023), would therefore greatly improve the resolution of eQTL-mapping analysis with single-cell sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…scRNA-seq can be used to recognize natural genetic variations allowing simultaneous genotyping and the acquisition of gene expression. This method has been recently reported as a preprint at the time of writing for S. cerevisiae to investigate allele-specific transcriptional heterogeneity and the complex interaction between eQTL and cell cycle phases (Boocock et al, 2023).…”
Section: Insights and Discoveries: What Have We Learned So Far?mentioning
confidence: 99%